Information Mechanics: The Dynamics of "It from Bit" (Global Journal of Science Frontier Research, 2021)
Abstract not found
Keywords: information mechanics; hierarchy problem; cosmological constant problem; dark matter; dark energy; black hole; it from bit; grand unification theory